Doping effects of metal cation on sulfide solid electrolyte/lithium metal interface. (June 2021) - Wang, Zhixuan; Jiang, Yong; Wu, Juan; Jiang, Yi; Ma, Wencheng; Shi, Yaru; Liu, Xiaoyu; Zhao, Bing; Xu, Yi; Zhang, Jiujun
Abstract: Doping modification is usually used to improve the ionic conductivity of sulfide solid electrolytes, but its effects on the interface between the electrolyte/lithium (Li) metal seem not sufficiently studied and understood. In this work, the advantages and disadvantages of sulfide electrolyte doped with MoS2, ZnS, FeS2, SnS2 and SiS2 are systematically studied. The ab initio molecular dynamics (AIMD) calculations and experiments show that MoS4 4- can preferentially replace the P2 S7 4- in Li7 P3 S11, thereby broadening Li + channels and creating Li vacancies to promote ion conduction. However, the doping of MoS2 can lead to the introduction of Mo metal into the solid electrolyte/Li interface layer (SEI), resulting in the reduction of the SEI's interface energy and migration rate of Li atoms at SEI, as well as the accumulation of electrons, thereby accelerating the thickening of the SEI and growth of Li dendrites. The doping results of different sulfides show that the critical current density is positively related to the resistivity of the doping element. The doping of non-metallic silicon will not cause a decrease in the critical current density. This work provides an important reference for the selection of solid electrolyte dopants and the construction of electrolyte/Li interface. Graphical Abstract: ga1 Highlights: Metal cations doping of Li7P3S11 will replace P2S74- and increase ion conductivity. Metallic Mo will reduce interface energy and increase Li diffusion barrier of SEI, accelerating Li dendrites growth. Mo will turn SEI into a mixed conductor of ions and electrons, thus thickening SEI. Critical current density is positively correlated with resistivity of the doping elements, rather than ion conductivity. Non-metallic Si-doping will cause an increasement in electrochemical performance.